2005
DOI: 10.1007/s10152-004-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the spatial relationship between sponges and macroalgae in sublittoral rocky bottoms: a descriptive approach

Abstract: Because sublittoral sponges of temperate areas are usually more abundant at sites with low algal abundance, there is the widespread notion that macroalgae out-compete and displace sponges to habitats less suitable for algal proliferation. In this study, based on 292 sampling quadrats, we collected a total of 87 demosponge species and examined the level at which sponge distribution pairs with a variety of alga-dominated and animal-dominated habitats occurring in three zones located across a marked in-bay/out-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 14 publications
4
31
1
Order By: Relevance
“…In contrast, only a few sponge species were positively correlated with algae. This is in contrast to what was reported for the Mediterranean by Preciado & Maldonado (2005), where a higher proportion of species were strongly correlated with algal abundance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, only a few sponge species were positively correlated with algae. This is in contrast to what was reported for the Mediterranean by Preciado & Maldonado (2005), where a higher proportion of species were strongly correlated with algal abundance.…”
Section: Discussioncontrasting
confidence: 99%
“…Konar & Iken (2005) proposed that the dominance of algae over sponges on the tops of boulders was the result of micro-habitat differences among surface orientations, including differences in sediment load and light intensity, preventing sponges from occurring on horizontal surfaces (Wilkinson & Vacelet 1979, Maldonado et al 2008). More recently, Preciado & Maldonado (2005) found that substratum inclination strongly correlated with sponge and algal distribution patterns, suggesting that substratum inclination was the main factor structuring sponge assemblages in the shallow waters of the Mediterranean. These authors found that sponges were mostly restricted to overhangs, where factors considered to be detrimental to sponges (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent negative associations between temperate sponges and macroalgae on subtidal hard substrata have indicated restriction of sponges to sites that are less favorable to algae (e.g., Witman and Sebens 1990;Bell 2002). Recently, Preciado and Maldonado (2005) have advised caution in interpretation of negative association patterns. By a variety of analyses they demonstrated that, although sponges and macroalgae were sometimes negatively associated, variation in distribution and abundance of sponges among their sites on the north Atlantic coast of Spain was best explained by substratum inclination (i.e., horizontal, vertical, overhangs, or ceilings).…”
Section: Competition Between Sponges and Other Organismsmentioning
confidence: 99%
“…Concerning sponges, encrusting common species were massive (like Cliona celata, Tethya aurantium, Pachymatisma johnstonia) and then easy to count. We used 0.25 m -2 (0.5 9 0.5 m) quadrats for sampling to maximize accuracy in the quantification of species (Edwards 1998;Kautsky et al 1999;Martin 1999;Davies et al 2001;Neto 2001;Eriksson et al 2002;Mercer et al 2003;Preciado and Maldonado 2005;Rinde and Sjøtun 2005). This quadrat size allowed the diver to make accurate in situ qualitative and quantitative readings.…”
Section: Study Sites and Sampling Designmentioning
confidence: 99%